Role of Listeriolysin O in Cell-to-Cell Spread of Listeria monocytogenes - Gedde, Margaret M. (American Society for Microbiology, 2000)
Listeria monocytogenes is a facultative intracellular bacterial pathogen that escapes from a host vacuolar compartment and grows rapidly in the cytosol. Listeriolysin O (LLO) is a secreted pore-forming protein essential for the escape of L. monocytogenes from the vacuole formed upon initial internalization. However, its role in intracellular growth and cell-to-cell spread events has not been testable by a genetic approach. In this study, purified six-His-tagged LLO (HisLLO) was noncovalently coupled to the surface of nickel-treated LLO-negative mutants. Bound LLO mediated vacuolar escape in approximately 2% of the mutants. After 5.5 h of growth, cytosolic bacteria were indistinguishable from wild-type bacteria with regard to formation of pseudopod-like extensions, here termed listeriopods, and spread to adjacent cells. However, bacteria in adjacent cells failed to multiply and were found in double-membrane vacuoles. Addition of bound LLO to mutants lacking LLO and two distinct phospholipases C (PLCs) also resulted in spread to adjacent cells, but these triple mutants became trapped in multiple-membrane vacuoles that are reminiscent of autophagocytic vacuoles. These studies show that neither LLO nor the PLCs are necessary for listeriopod formation and uptake of bacteria into neighboring cells but that LLO is required for the escape of L. monocytogenes from the double-membrane vacuole that forms upon cell-to-cell spread.